Evaluation of The Implementation of Standard Operating Prosedures (SOP) In Term Of Excellent Service By Customer Service Officer At Grapari Garuda Telkomsel Surabaya - Retno Puspita Sari; Chitra Laksmi Rithmaya (International Journal of Science and Environment (IJSE), 2025)
Increasingly competitive business competition in this era makes service quality an important factor in maintaining customer loyalty. This study aims to determine the implementation of standard operating procedures (SOPs) for excellent service by GraPari Telkomsel Garuda Surabaya customer service. The research method used in this study is a qualitative approach through observation at GraPari Telkomsel Garuda Surabaya. The results of the study indicate that GraPari Telkomsel Garuda Surabaya has standard operating procedures (SOPs) for excellent service that regulate the workflow of customer service in providing services, from greeting customers, identifying needs, service processes, handling complaints, to closing services. The implementation of standard operating procedures (SOPs) for excellent service at GraPari Telkomsel Garuda Surabaya has been consistent, however, there are still weaknesses and challenges in its implementation, such as a lack of clarity regarding appearance guidelines for customer service representatives at GraPari Telkomsel Garuda Surabaya and customer service representatives who also serve as cashiers.